Pengabdian Masyarakat Internasional: Membangun Koneksi Global, Volunteer Pariwisata, Pendidikan dan Kesehatan Internasional - Btari Mariska Puwaamijaya; Syti Sarah Maesaroh; Adi Prehanto; Muhammad Dzikri Ar Ridlo; Ni Wayan Mega Sari Apri Yani; Ni Made Ayu Natih Widhiarini; I Wayan Putra Aditya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This service aims to advance the achievement of Sustainable Development Goals (SDGs) number 4 (Quality Education) and 10 (Reducing Equality) with a focus on developing the competence of foreign volunteers and improving the management of the Widya Guna Disability Foundation. Collaboration between the UPI Tasikmalaya Digital Business Program, the Bali Institute of Tourism and International Business, and PT Medika Nusantara (Medi-Call) is the main vehicle for this activity. The main theme of the service is "Building Global Connections: International Volunteer Tourism, Education, and Health," which involves information sessions, focus group discussions (FGD), as well as the active participation of foreign volunteers from various countries. It is hoped that the results of this service can contribute to increasing access to education for individuals with disabilities (SDGs number 4) as well as encouraging social and economic inclusion (SDGs number 10) through strengthening the management of the Widya Guna Disability Foundation. This kind of collaboration strengthens the spirit for sustainable positive change at the global level and inspires closer cooperation in the future. Keywords: Service, SDGs, Foreign Volunteers, Disability Foundation, Management, Education, Equality, Social Inclusion.